Wavelet domain control of rotor vibration - M. O.T. Cole (2018)
This paper describes a novel application of the real-time wavelet transform in the control of rotor vibration. Vibration signal wavelet coefficients that relate to different time scales provide direct information on the system dynamic state, and can thus be used for feedback in a closed-loop control strategy that attenuates both transient and steady-state vibration components. Control force signals are synthesized from basis functions having a characteristic frequency and spacing interval closely matched to the rotational frequency. The control signal basis coefficients are generated by integral feedback of the wavelet coefficients such that under steady-state conditions the control forces eliminate measured rotor vibration. The controller synthesis problem is solved by iterative solution of a linear matrix inequality to obtain a gain matrix that satisfies H∞norm-bound specifications for transient vibration attenuation. It is demonstrated experimentally that wavelet coefficients from multiple scale levels can be used in direct feedback to reduce levels of transient vibration caused by instantaneous changes in unbalance. © IMechE 2006.